Sodium alginate/gelatin wet-spun fibers as a delivery platform for Nisin Z controlled release: antibacterial features against Staphylococcus aureus - Homem, Natália Cândido (2021)
[Excerpt] The aim of this study was to produce SA/GN microfibers via wet-spinning technique, and subsequently functionalize these fibers with Nisin Z, in order to map Nisin Z’s controlled release kinetics and antimicrobial action against S. aureus